Business Plan for The Development of Triple D Boarding House: Establishing A One-Stop Shopping Ecosystem - Cecep Supriadi; Meriza Hendri (Dinasti Review, 2025)
The boarding house business is a rapidly growing property sector in Indonesia's urban areas, driven by a high urbanization rate that saw the urban population increase to 56.7% by 2022, and the concentration of educational and office centers. Bandung, as a major educational city with over 305,000 active students and an estimated market potential reaching IDR 1.53 trillion annually, has become a strategic and attractive location for investors. This trend is further amplified by a digital shift, with reports indicating that 72% of tenants in Bandung now use online platforms to find accommodation. However, this industry faces challenges from intense competition, rising consumer expectations for adequate facilities, and a market shift towards housing that is not only functional but also supports a productive and community-oriented lifestyle. This study aims to develop a business plan for the expansion of Triple D Kos by opening a new branch with a